Faceted taxonomy for accessing digital libraries - Benildes, Maculan C. M. S.; Gercina, Lima A. B. O. (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
We present the development of a faceted taxonomy of scientific works and the use of this taxonomy in a system for searching a digital library of theses and dissertations (DLTD). We also propose an algorithm for indexing these documents. Our algorithm eases the retrieval of information contained in this kind of document, and offers structured information in which results have already been refined for the user. Our methodology is based on: a) domain analysis theory; b) facet analysis theory; and c) content analysis methods, including the categorical thematic analysis technique of Bardin (2009) and the methodology proposed by Moraes (1999). The faceted taxonomy we developed is the simplified representation of the thematic content of the documents. Keywords